United States : Financial Sector Assessment Program-Anti-Money Laundering And Combating The Financing Of Terrorism (Aml/Cft)-Technical Notes. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for the United States in the areas of anti-money laundering and combating the financing of terrorism (AML/CFT). The United States' AML/CFT legal and institutional framework has yet to address deficiencies identified in the most recent Financial Action Task Force mutual evaluation report regarding ownership information for U.S. corporations and trusts. In particular more rapid progress is needed to enhance transparency of legal persons to bolster financial system integrity. Trusts have a different legal and institutional framework, and draft regulations have been produced to strengthen financial institutions' obligations. These measures are however progressing slowly.